Development and validation of an analytical procedure for the determination of residual protein A in active substances of therapeutic monoclonal antibodies - E. V. Nozdrina; D. A. Mazalev; D. R. Rogozina; S. P. Zhivoderov; I. V. Lyagoskin; R. R. Shukurov (Биопрепараты: Профилактика, диагностика, лечение)
SCIENTIFIC RELEVANCE. An important quality-control issue for therapeutic monoclonal antibodies (mAbs) is the determination of residual protein A leaching from the carrier during the purification of mAbs by affinity chromatography. However, unrelated compounds (immunoglobulins) present in the sample can complicate the immunoenzymatic detection of protein A (matrix effect), potentially leading to false-negative test results. To increase the efficiency of enzyme-linked immunosorbent assay (ELISA), it is necessary to develop a sample preparation step that can irreversibly break the bond in the protein A–mAb complex.AIM. This study aimed to develop and validate an analytical procedure for the determination of residual protein A in active substances of therapeutic mAbs by ELISA with a test kit comprising in-house reagents.MATERIALS AND METHODS. Recombinant protein A was used as an antigen. Polyclonal antibodies to protein A were produced by immunising chickens, selecting immunised eggs, and isolating antibodies from these eggs. Protein A-specific antibodies were purified by affinity chromatography. Residual protein A was determined using sandwich ELISA with preliminary sample preparation. The analytical procedure was validated in accordance with the requirements of the State Pharmacopoeia of the Russian Federation (Validation of Analytical Procedures, OFS.1.1.0012).RESULTS. The authors obtained, isolated, and purified chicken IgY antibodies to recombinant protein A. The authors selected sample preparation conditions for the determination of residual protein A by ELISA and optimum compositions of buffer solutions, including the composition of a denaturing buffer to disrupt the protein A–mAb complex. The developed analytical procedure was validated. According to the measurements of protein A, the accuracy of the analytical procedure ranged within 83–108% of the nominal value, the interlaboratory precision ranged within 96–116%, and the repeatability was up to 13%. The lower limit of quantitation was 10 ng/mL with a minimum required dilution of 1:10. The analytical range extended from 10 to 40 ng/mL. The analytical procedure showed results comparable to those obtained with a similar test kit from an international manufacturer.CONCLUSIONS. The developed analytical procedure for the determination of residual protein A by ELISA with a test kit comprising in-house reagents can minimise the matrix effect in therapeutic mAbs. This analytical procedure will alleviate import substitution and reduce quality control costs for Russian immunobiologicals.